2008
DOI: 10.1016/j.jpsychores.2008.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Reduced parasympathetic activity during sleep in the symptomatic phase of severe premenstrual syndrome

Abstract: Objective-Severe premenstrual syndrome (PMS) is a common, distressing disorder in women that manifests during the premenstrual (late-luteal) phase of the ovulatory menstrual cycle. There is some evidence that altered autonomic function may be an important component of PMS but few studies have used heart rate variability (HRV), as a sensitive marker of autonomic activity, in severe PMS and findings are conflicting.Methods-We investigated HRV during sleep, a state relatively free of external disruptions, in nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 35 publications
2
40
1
Order By: Relevance
“…Menstrual cycle-related discomfort, such as premenstrual syndrome and premenstrual dysphoric disorder, influences the autonomic nervous system. 17,[19][20][21] However, scores from the menstrual distress questionnaire 22 the participants had answered in the follicular (the fifth to the 11th day from the first day of menstruation) and the late-luteal phase (within 7 days before the next menstruation) revealed that none of the participants had premenstrual disorders. The medical examination and interview further clarified that no participants had any other gynecologic or psychiatric disorders.…”
Section: Participantsmentioning
confidence: 99%
“…Menstrual cycle-related discomfort, such as premenstrual syndrome and premenstrual dysphoric disorder, influences the autonomic nervous system. 17,[19][20][21] However, scores from the menstrual distress questionnaire 22 the participants had answered in the follicular (the fifth to the 11th day from the first day of menstruation) and the late-luteal phase (within 7 days before the next menstruation) revealed that none of the participants had premenstrual disorders. The medical examination and interview further clarified that no participants had any other gynecologic or psychiatric disorders.…”
Section: Participantsmentioning
confidence: 99%
“…However, sometimes, it may be associated with other signs, causing physical and mental problems for women. This kind of physical, mental, and emotional symptoms that appear before menstruation and disappear at the beginning of the menstruation period is called premenstrual syndrome [1].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies proposed a possible role of the automatic nervous system in its pathology and it was reported that women with PMDD have a higher level of no epinephrine compared to that of normal women [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study by F.C. Baker et al showed significant reduction in parasympathetic activity during sleep in women with severe PMS in the late-luteal phase of menstrual cycle [1].…”
mentioning
confidence: 96%